Effect of Pre‐Deformation and Subsequent Aging on the Damping Capacity of Mn‐20 at.%Cu‐5 at.%Ni‐2 at.%Fe alloy. Issue 9 (16th February 2015) - Jiazhen, Yan; Ning﻿, Li; Xu, Fu; Wenbo, Liu; Ying, Liu; Xiuchen, Zhao
<x xml:space="preserve">Abstract</x> In the paper, the effect of pre‐deformation and subsequent aging treatment on the damping capacity and microstructure of Mn‐20 at.%Cu‐5 at.%Ni‐2 at.%Fe (M2052) alloy is investigated. The logarithmic decrement (δ) of the specimens with various pre‐deformation degrees is determined to discuss the change of damping capacity before and after aging process. Meanwhile, the martensite and twinning structures with different deformation degree are comparatively studied. The results suggest that the δ of the alloy decreases rapidly and the martensite plates are rearranged and become thinner with increase in deformation degree. Reasons accounting for the decrease are discussed and attributed to the internal stress field introduced during the deformation process which hinders the motion of the twin and phase boundaries. In addition, aging at 435 °C for 20 min leads to a recovery of the damping capacity of the pre‐deformed M2052 alloy. However, the recovery is highly dependent on the pre‐deformation degree. The damping capacity of the specimens with a deformation less than 5% can be completely recovered after aging, while the others with a deformation exceeds 5% can be just partly recovered.